2013
DOI: 10.3758/s13415-013-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the anterior insula are associated with the likelihood of financially helping versus harming others

Abstract: The neural basis of individual differences in positive and negative social decisions and behaviors in healthy populations is yet undetermined. Recent work has focused on the potential role of the anterior insula in guiding social and nonsocial decision making, but the specific nature of its activation during such decision making remains unclear. To identify the neural regions mediating individual differences in helpful and harmful decisions and to assess the nature of insula activation during such decisions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Previous studies found that greater empathy‐related neural responses in the AI promoted prosocial behaviors [Hein et al, ; Masten et al, ]. For example, participants with greater activation in the AI were less likely to financially harm a charity [Greening et al, ]. Given the evidence mentioned above, the AI might play a crucial role in integrating altruistic goals in the deceptive decision‐making process.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies found that greater empathy‐related neural responses in the AI promoted prosocial behaviors [Hein et al, ; Masten et al, ]. For example, participants with greater activation in the AI were less likely to financially harm a charity [Greening et al, ]. Given the evidence mentioned above, the AI might play a crucial role in integrating altruistic goals in the deceptive decision‐making process.…”
Section: Introductionmentioning
confidence: 97%
“…Although we observed only a marginally significant univariate effect between the CS+ and CS− in right S1, this analysis is orthogonal to the individual differences approach that is the focus of the current study. Indeed, a number of papers have found individual differences in brain activity despite an absence of univariate effects [ 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neural responses in the AI predicted affective empathy for beneficiaries, while temporoparietal junction (TPJ) activity was associated with the degree of cognitive perspective taking, suggesting that these distinct paths of social cognition and psychological mechanisms differentially lead to intraindividual and interindividual heterogeneities in charitable giving. Indeed, there was specific neural evidence of a correlation between individual differences in helpful decisions and the neural activation of AI, ACC, and TPJ ( Greening et al, 2014 ), and neural mechanisms of individual differences in empathy and pro-social behaviors were further revealed by reinforcement learning theory ( Lockwood et al, 2016 ). However, how affective empathy is linked to pro-social behaviors in charitable giving and the neural circuitry underlying empathy in terms of multi-faceted cognitive and emotional process remain poorly understand.…”
Section: Empathy/charitable Givingmentioning
confidence: 99%